ISW for the Treatment of Deviated and Rotated Teeth - HUANG, Chun-shuo; YU, Jian-hong (International Journal of Innovative Research in Medical Science, 2019)
The objective of the case study is for the treatment of deviated and rotated teeth by ISW (Improved Super-elastic Ti-Ni alloy wire, developed by Tokyo Medical and Dental University). An adult female (37 years old) came to our clinic with a chief complaint of abnormal tooth axis of lower arch combined with spacing and rotation of other teeth. This patient mentioned she didn’t care about the problem of facial asymmetry. By using ISW, lower deviated teeth were corrected rapidly. Rotation of lower left and right premolars were corrected simply by ISW leveling. For correction of rotated upper left second premolar, we placed a bracket on the mesial surface of #25 temporarily and Ni-Ti open coil-spring was placed in between #25 and #26 in order to increase inter-bracket span so as to create space for bracket bonding on the buccal surface. ISW was fully engaged into #25 and then rotation was corrected by further leveling. After 18 months of active treatment, a stable occlusion and a desirable esthetic outcome was achieved and the patient was pleased with the treatment result after the active treatment.